A study to evaluate behavior of society with Covid-19 Frontline health workers - Golhar, Mayuri; Yadav, Tarun; Walia, Harsimran Singh; Johar, Sanjay (Asian Journal of Medical Sciences, 2021)
Background: Health care workers caring for Covid-19 patients go through mental stress, physical exertion, stigma from society and the fear of losing patients’ and colleagues. Aims and Objective: To evaluate frontline health care workers perspective about the society’s behavior towards them. Materials and Methods: This questionnaire-based study included a total of 648 participants and included 20 questions about demography, Covid duty, health related issues and behavioral aspect of society during Covid duty. Behavioral related responses were scaled on the basis of response score. Results: Suggested that the overall population behavior was satisfactory but behavioral biases were existent. Major health issue of concern that surfaced during duties was stress. Conclusion: Behavioral prejudices are existent due to the stigma attached to this pandemic and hence needs to be addressed with great concern. Health related issues should be dealt promptly and psychological counseling should be made mandatory.